PENGARUH CORPORATE GOVERNANCE TERHADAP PRAKTIK MANAJEMEN LABA (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2010-2012) - Annastacya Maria Bonita; Rahardja Rahardja (Diponegoro Journal of Accounting, 2014)
The purpose of this study was to examine the effect of corporate governance on the earnings management.  Indicators used to measure corporate governance mechanisms in this study is the managerial ownership,institusional ownership, audit quality, and meeting frequency of audit comittee. While, earning management as the dependent variable was measured using a cash flow statement approach. This study uses secondary data with entire population of manufacturing companies listed in the Indonesia Stock Exchange (BEI) in 2010-2012.  The method used to determine the sample using purposive sampling.  The analytical method used is multiple linear regression, regression testing prior to first tested the classical assumptions.The results of hypothesis testing showed that the managerial ownership did not significantly affect earnings management  .Other result, institusional ownership and audit quality showed  negatively affects the earning management. While, the frequency of meetings of audit comittee showwed positively effect on earnings management.